ASPEK YURIDIS PASAR MODAL SEBAGAI SARANA PEMBIAYAAN DAN PENGEMBANGAN PERUSAHAAN - Suradiyanto Suradiyanto (Yuriska: Jurnal Ilmiah Hukum, 2018)
Parties that require investment fund is not limited to the government alone, but also other productive sectors of the private sector. If the government usually acts as an initiative taker physical infrastructure development, the private sector (individuals and companies) to act as a driver of economic activity such as attempts commercial production of goods and services calculated based on pure business will be profitable. All this requires a good investment fund short-term nature, such as working capital for the cost of operational needs, as well as long-term funds such as for procurement of fixed assets required. In order to meet the needs of the company will fund as a means of financing and development can be done through various options of financing the company and one of the company's financing alternatives can be done by finding others to participate invest in the company. This can be done by selling the majority ownership of the company to the general public by way of public offering (go public) through the capital market. Initial public offerings made by the company through the capital market can make the company receives cash from the public which can then be used by the company for financing and development of the company